Development of Stem-Based Flipbook on Biodiversity Materials to Train Critical Thinking Skills for X-Grade Students of Senior High School - Wimawantika Hapsari Nugraha; Fida Rachmadiarti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2022)
One of the skills of students in learning activities in 21st century education is critical thinking skills. Critical thinking skills can be developed by means and appropriate learning resources. The COVID-19 pandemic condition requires the distance learning process (PJJ) of course to require learning resources that can be accessed by teachers and students even though they are not in one place. One of the learning resources used in the learning process is electronic media, one of which is flipbook. Flipbook is an electronic book that is presented digitally and can be flipped that contains text, images, audio, video, and hyperlinks. Flipbook contains various features that can be used as learning resources for students on biodiversity material and can train students to think critically. The purpose of this research was produced a valid and practical STEM-based flipbook (Science, Technology, Engineering, Mathematics). Research used 4D models (Define, Design, Develop, and Disseminate stage) but Disseminate stage was not carried out. The theoretical feasibility of the flipbook was obtained from validation by expert lecturers, namely material and education expert lecturers and high school biology teachers. Flipbook validation was measured based on presentation, content, and linguistic aspects. The practicality test was evaluted based on student's responses collected by questionnaire of 13 students X MIA 4 SHS 14 Surabaya. The analysis technique was quantitative descriptive. The flipbook was said to be very feasible with a validity result of 90.75 % with very valid criteria. Flipbook is also stated to be very practical based on the results of the student response questionnaire of 93.1% with very practical criteria. It can be concluded that the flipbook based on STEM (Science, Technology, Engineering, Mathematics) on biodiversity material to train critical thinking that has been developed is declared valid and practical.